2008
DOI: 10.1136/bjsm.2008.054189
|View full text |Cite
|
Sign up to set email alerts
|

The role of community programmes and mass events in promoting physical activity to patients: Table 1

Abstract: The challenge for physical activity promotion in clinical contexts is finding ways of encouraging patients to become more active. Brief advice in primary care is effective, in the short term, in increasing physical activity, but is only provided by a few clinicians on a regular basis. The possibilities for public health approaches include others in the practice providing brief advice, or referral to community facilities and programmes. Even these have limited evidence regarding their population reach. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 20 publications
0
59
0
Order By: Relevance
“…This article builds on previous investigations of whether mass events are merely one-off public spectacles or potential public health interventions (Bauman, Murphy, & Lane, 2009;Murphy & Bauman, 2007). An updated search was undertaken using the criteria described by Murphy and Bauman (2007) of published literature on sport and physical activity events and campaigns, as well as unpublished reports from government agencies and research centres.…”
Section: Introductionmentioning
confidence: 98%
“…This article builds on previous investigations of whether mass events are merely one-off public spectacles or potential public health interventions (Bauman, Murphy, & Lane, 2009;Murphy & Bauman, 2007). An updated search was undertaken using the criteria described by Murphy and Bauman (2007) of published literature on sport and physical activity events and campaigns, as well as unpublished reports from government agencies and research centres.…”
Section: Introductionmentioning
confidence: 98%
“…Although it has been suggested that MPSEs could increase population physical activity, 3 such events could inspire short-term motivation which would not support long-term physical activity. 5,9,12 Previous evidence shows that when MPSE participants were more satisfied with their event experience, they held stronger attitudes toward regular physical activity.…”
Section: What Is Already Known On This Topic?mentioning
confidence: 99%
“…Mass participation sports events (MPSEs) are a proposed way to promote physical activity. 3 Non-elite MPSEs are events in which "the primary focus is on promoting participation and engagement rather than the significance of the sporting outcome". 4 There is limited evidence that MPSEs have broad appeal to people who are newly or infrequently active.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mass participation events involving exercise (e.g. charity bicycle rides and fun runs) have been suggested as a potential public health resource by motivating physical activity via social engagement [8].…”
Section: Introductionmentioning
confidence: 99%